1982
DOI: 10.2307/2232552
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Role of Commodity Storage

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(91 citation statements)
references
References 10 publications
1
88
0
2
Order By: Relevance
“…Subsequent numerical models in the Gustafson tradition, including Johnson and Sumner (1976), Gardner (1979), Newbery and Stiglitz (1981, Ch. 30) and Wright and Williams (1982) have confirmed that qualitative features of the price behavior of some important commodities are consistent with the effects of such arbitrage. In addition, numerical storage models (for example, Park 2006) can explain key qualitative features of peasants' economic behavior when they face high transaction costs, and the threat of hunger if local food crops fail and prices soar.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…Subsequent numerical models in the Gustafson tradition, including Johnson and Sumner (1976), Gardner (1979), Newbery and Stiglitz (1981, Ch. 30) and Wright and Williams (1982) have confirmed that qualitative features of the price behavior of some important commodities are consistent with the effects of such arbitrage. In addition, numerical storage models (for example, Park 2006) can explain key qualitative features of peasants' economic behavior when they face high transaction costs, and the threat of hunger if local food crops fail and prices soar.…”
Section: Introductionmentioning
confidence: 56%
“…It is clear that this specification, and the others considered in Gustafson (1958a,b), Gardner (1979), Wright and Williams (1982), Williams and Wright (1991) and Deaton and Laroque (1992, Table 2, p. 11), in fact imply lower price variation than observed in major commodity markets. Although it is conceivable that variation in production has been substantially underestimated, it appears more likely that the consumption demand functions specified in the numerical models, with price elasticities (at consumption equal to mean production) in the range −0.5 to −0.1, are more sensitive to price than are consumption demands in the markets we consider.…”
Section: Can Storage Generate High Serial Correlation?mentioning
confidence: 66%
See 2 more Smart Citations
“…Instead, my support the importance of models that take into account demand shocks due to world GDP such as Dvir and Rogoff (2010), Mitraille andThille (2009), Bodenstein et al (2012). My work also points to demand rather than supply shocks as an interpretation of shocks in competitive storage models (Gustafson, 1958a,b;Wright and Williams, 1982).…”
Section: ) Andmentioning
confidence: 91%